Investigating the initiation & progression of ulcerative colitis - Fair, Kathryn L. (2024)
Inflammatory bowel disease (IBD) is a significant and ever-growing problem in developed countries, with recent increased prevalence throughout Eastern countries. It is an idiopathic, progressive disease characterised by chronic GI inflammation, the aetiology of which remains largely unknown. Inflammatory phenotypes differ between healthy & IBD patients with dysregulated immune responses suspected to play a critical role in disease pathogenesis.